Comparative study of direct and indirect composite veneers in terms of marginal gap and microleakage / Lim Yee Ping - Lim, Yee Ping (2019)
Objectives To evaluate the microleakage and marginal gap at cervical and incisal margin of direct and indirect composite veneers. Materials and method: Forty-four extracted human maxillary central incisors (n=44) used for the study were chosen based on the inclusion and exclusion criteria. They were randomly divided into two groups. Group 1: Shofu Beautifil™ direct composite (Shofu Inc. Kyoto, Japan) and Group 2: Shofu Ceramage™ indirect composite (Shofu Inc. Kyoto, Japan). Putty index for each tooth was taken before it was subjected to preparation for veneer restorations. The manufacturer’s instructions for handling and application procedures for both materials were strictly followed. All the samples were stored under water for 24 hours at 37 ° C, then subjected to thermo-cycling (500 cycles at the temperature between 5° and 55° C for 60 seconds in water baths (according to ISO 11450). Upon completion of artificial ageing, the entire external surface of the restoration and the supporting crown and root excluding the margins of the veneers were coated with two layers of nail varnish before being immersed in 2% basic fuschine dye for 24 hours. All the specimens were mounted in acrylic resin and sectioned labio-palatally at the middle of the restorations. Each half of the sectioned specimens for both direct and indirect composite veneers were observed under a stereomicroscope (×40 magnifications) and the degrees of dye penetration at the cervical and incisal margins were measured in micrometers (µm). Marginal gaps were measured at the cervical and incisal areas by viewing the specimens under stereomicroscope OLYMPUS™ (40X) for both the groups and the reading were measured in micrometers (µm) by one assessor. To control the iv reproducibility of the scoring system and the intra-examiner performance, the samples (n=44) were measured again one month after initial measurement. The reproducibility was tested using intraclass correlation coefficient. Mann-Whitney Test was used to determine any significant differences in microleakage and marginal gap of direct and indirect composite veneer. Wilcoxon Signed Rank test was used to evaluate intragroup differences for microleakage and marginal gap at the cervical and incisal margins for both the groups. Spearman’s correlation test was used to correlate the association of microleakage and marginal gap at the cervical and incisal margins of direct and indirect composite veneers (p>0.05). Results Mann-Whitney U test revealed that direct composite veneers demonstrated significantly lower microleakage and marginal gap at cervical and incisal area when compared to indirect composite veneers (p< 0.001). Wilcoxon signed rank test showed that there were no significant intragroup differences for microleakage and marginal gap at cervical and incisal margins for both direct and indirect composite veneers (p< 0.05). Spearman correlation test revealed that there was a positive correlation between marginal gap and microleakage at the cervical and incisal portion of the direct and indirect composite veneers and the tooth structures (p< 0.001). Conclusion: Within the limitation of this study, direct composite veneers Beautifil™ (Shofu Inc. Kyoto, Japan) shown to be superior than the indirect composite veneers, Ceramage™ (Shofu Inc. Kyoto, Japan) by means of less marginal gaps and microleakage. There was a direct correlation between the existence of marginal gaps and microleakage, when there v was less marginal gap between tooth-restoration interface there was less microleakage. Key words: composite veneer, microleakage, marginal gap.